2015
DOI: 10.1111/echo.12988
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Function in Children before and after Autologous Peripheral Blood Stem Cell Transplantation

Abstract: TDI detected subtle abnormalities in systolic and diastolic functions before and after HSCT, which suggests that a conditioning regimen may affect cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
4
9
0
Order By: Relevance
“…In a pediatric cohort suffering from atrial tachycardia, Ge et al 2 found that left ventricular (LV) function assessed with the TDI parameter Sm advances an early detection of LV dysfunction. In agreement to ElMarsafawy et al, 1 Klitsie et al 3 found that TDI parameters were able to detect subclinical impairment of systolic biventricular function in children with congenital heart defects. ElMarsafawy et al 1 investigated children with an age range of 3-14 years and found that both, the Sm and the S 0 values, were significantly reduced in patients undergoing HSCT compared to the control group.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In a pediatric cohort suffering from atrial tachycardia, Ge et al 2 found that left ventricular (LV) function assessed with the TDI parameter Sm advances an early detection of LV dysfunction. In agreement to ElMarsafawy et al, 1 Klitsie et al 3 found that TDI parameters were able to detect subclinical impairment of systolic biventricular function in children with congenital heart defects. ElMarsafawy et al 1 investigated children with an age range of 3-14 years and found that both, the Sm and the S 0 values, were significantly reduced in patients undergoing HSCT compared to the control group.…”
supporting
confidence: 73%
“…With great interest, we have read the article, "Assessment of Myocardial Function in Children before and after Autologous Peripheral Blood Stem Cell Transplantation" from ElMarsafawy et al 1 They performed a prospective casecontrol study of 19 children (compared with an age-matched control group) who were undergoing a peripheral hematopoietic stem cell harvest and planned high-dose conditioning chemotherapy with autologous peripheral blood stem cell transplantation (HSCT). 1 Before and 3 months after the HSCT, the presence of a possible functional myocardial impairment was investigated with the use of the tissue Doppler imaging (TDI) parameters, peak mitral annular systolic velocity (Sm), and tricuspid annular peak systolic velocity (S 0 ). In a pediatric cohort suffering from atrial tachycardia, Ge et al 2 found that left ventricular (LV) function assessed with the TDI parameter Sm advances an early detection of LV dysfunction.…”
mentioning
confidence: 99%
“…Studies of both pediatric and adult patients have shown reductions in cardiac function in a subset of patients soon after HSCT . While short‐term changes to function may not necessarily predict long‐term cardiac outcome, they do demonstrate HSCT to be a cardiotoxic procedure for a subset of patients.…”
Section: Causes Of Cardiac Injurymentioning
confidence: 99%
“…In children who receive anthracyclines, changes in ventricular wall thickness likely precede overt changes in shortening fraction or ejection fraction . In children, tissue Doppler imaging has been used to identify subtle abnormalities in systolic and diastolic functions 3 months after autologous HSCT; however, it is not known whether these changes persist for long term . Speckle‐tracking echocardiography is a means of tracking movement patterns to determine tissue motion and deformation, which can then be quantified as a measure of strain.…”
Section: Detecting Cardiac Injurymentioning
confidence: 99%
See 1 more Smart Citation